2020
DOI: 10.1111/petr.13709
|View full text |Cite
|
Sign up to set email alerts
|

Promoting medication adherence from the perspective of adolescent and young adult kidney transplant recipients, parents, and health care professionals: A TAKE‐IT TOO study

Abstract: Medication non‐adherence is an important factor limiting allograft survival after kidney transplantation in AYA. Some interventions, including the TAKE‐IT, showed some success in promoting adherence but the potential for scalability and use in routine clinical practice is limited. We applied user‐centered design to gather the perspectives of recipients, parents, and health professionals concerning their needs, challenges, and potential intervention strategies to design an optimal, multi‐component medication ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…Data saturation was reported in 53 (45%) studies, and use of qualitative software and member checking (providing preliminary findings to the participants for review) were reported in 40 (34%) and 28 (24%) studies, respectively. These studies performed member checking but did not report if and how patients contributed as co‐authors with exception of two studies where relevant stakeholders were co‐investigators 19,20 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data saturation was reported in 53 (45%) studies, and use of qualitative software and member checking (providing preliminary findings to the participants for review) were reported in 40 (34%) and 28 (24%) studies, respectively. These studies performed member checking but did not report if and how patients contributed as co‐authors with exception of two studies where relevant stakeholders were co‐investigators 19,20 …”
Section: Resultsmentioning
confidence: 99%
“…Some felt transplantation replaced one life with another different set of rules including the routine and regime of taking medications 23,40,51,56,66,84,93,95,99,103,120‐123 . Although patients often adjusted to the new medication regimens, some found it difficult to adjust and accept the need to take medications 19,20,21,29,32,33,52,54,57,60,65‐67,70,93,94,96,97,102,118,124,125 . They struggled with the “larger size” of pills, and the “avalanche of medicines” taken each day 56 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations